Hydrogen peroxide priming alleviates chilling stress in rice (Oryza sativa L.) by enhancing oxidant scavenging capacity - Sonya Afrin (Fundamental and Applied Agriculture, 2019)
Chilling is a substantial stressor for plants. In fact, some biochemical reactions involved in growth and development of plant are sensitive to temperature. In particular, chilling stress represents a severe issue for plant growth and productivity and strategies to alleviate the stress is an important goal for agriculturists. While, hydrogen peroxide (H2O2) acts as a signalling molecule and its role in preventing several abiotic stresses like heat, salinity, drought etc. is well understood. Thus, the present study tested the effects of H2O2 priming in mitigation of chilling stress at germination and seedling stage of rice. The rice seeds were treated with H2O2 (5, 10 and 15 mM H2O2) solution for 24 h and exposed to chilling stress either for 6 h in 24 h or 12 h in 24 h for 7 days. Results revealed that, chilling stress seriously impeded germination indices (germination percentage, germination rate index, coefficient of velocity of germination and mean germination time), morphological parameters (shoot length, root length and fresh weight), total chlorophyll content and antioxidant enzymes (catalase and ascorbate peroxidase) activity. On the other hand, priming with H2O2 (5mM, 10mM and 15mM) displayed protective effects on germination indices and growth parameters and conferred a significant tolerance against chilling stress. Priming with H2O2 also significantly protected chlorophyll from chilling-induced degradation. Our results provide a strong foundation that priming with H2O2 confers a positive physiological effect by enhancing antioxidant enzymes capability (increased catalase and ascorbate peroxidase activity) of chilling stressed rice plant. Among the concentrations, 10 mM H2O2 performed relatively better in chilling stress alleviation. Therefore, this technique can be used for improved rice seedling production in northern part of Bangladesh under low temperature condition. [Fundam Appl Agric 2019; 4(1.000): 713-722]